Factors Influencing The Performance Of Village Health Teams (VHTS) In Health Promotion. A Cross-Sectional Study Of Namuyoga Town Council Tororo District. - Aluma, Franco; Manyara, Arnold Bbee (Student's Journal of Health Research Africa, 2021)
Background: The study focused on examining the various factors, directly and indirectly, that influence the performance of VHT activities. The study was based on the scientific fact that incentives, availability, and support supervisions have a significant impact on the quality of health services offered by VHTS The study was conducted in Nabuyoga Town Council in Eastern Uganda. Methodology: The researcher adopted cross-sectional descriptive methods; the researcher employed a questionnaire with both ended and closed-ended questionnaires to gather data. Also, the researcher acquired an interview guide to gathering qualitative data. Results Substantively the study has revealed positive results, that incentives influence the performance of VHTS in terms of motivation and retention. Secondary the study has shown that lack of sufficient supplies has negatively affected the performance of service delivery in terms of availability and accessibility. Thirdly, the study has revealed there is a dire need to adopt an effective supervisory mechanism for technical development and the sustainability of VHT activities in the area. Conclusion and recommendations: Quality services delivery by VHTS in health promotion, there is a great need to improve on the availability of incentives, supplies, and support supervision; it is only by sincere involvement of community members that health quality in the area can be realized.